Gun island : a novel - Ghosh, Amitav (Penguin, 2019)
"It is in his hometown of Kolkata where Dr. Deen Datta meets, by chance, a distant relative who upends his world with the mention of a figure that has long haunted Deen's imagination--Bonduki Sadagar, the mysterious Gun Merchant of Bengali legend. A Brooklyn-based dealer in rare books, Deen, on the cusp of retirement, suddenly finds himself propelled into the depts of the snake-infested Sundarbans, in search of a shrine to the Merchant. Thus begins an unforgettable journey both inward and outward, and moving across continents. As Deen's journey progresses, he confronts a changing world and encounters a cast of characters who will unsettle everything he thought he kenw about himself. There is Piya, a fellow Bengali American who helps launch his journey; Tipu, an entrepreneurial young man who shows Deen the realities of growing up in today's world; Rafi, desperate to help those in need; and Cinta, an old friend who provides the missing link in the story that binds them all."--Dust jacket front flap.